(untitled) (Research, Society and Development, 2024)
Different heights of forage management modify the plant architecture, changing the proportion of young and mature tissues and its nutritional value. Thus, the objective of this study was to evaluate the tissue composition of leaves of hybrid Urochloa cv. Mulato II (syn. Brachiaria) kept under four management conditions simulating continuous grazing in the rainy and dry seasons. In addition, the effect of the variation of the percentage of tissues in the leaf on its digestibility was carried out based on the contents of crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF) and in vitro dry matter digestibility (IVDMD). Four stocking levels were evaluated simulating continuous grazing, with a canopy height of 10, 20, 30, and 40 cm. It was found that the pastures with 10 and 20 cm had the lowest percentage of lignified tissues in the rainy and dry seasons, which consequently resulted in greater tissue disappearance, mainly of the mesophyll. Pastures with 10 cm had higher CP contents, lower NDF and ADF contents, and consequently higher IVDMD. Therefore, the Mulato II grassland managed with 10 cm had greater degradability of the leaf tissues, due to the higher percentage of rapidly digestible tissues.